Between Past and Future - 1/8
Recording of the academic panel entitled “Meanings of 1989 and the Present Significance of the Past”, the second panel of the “Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" international conference that was held at CEU in March 1999. The chairman of the panel is Vladimir Tismăneanu. The tape contains the end of Prof. Jacques Rupnik’s speech, Prof. Tamás Gáspár Miklós’ full presentation and the first part of Prof. Karol Soltan’s speech.